2004
DOI: 10.1080/09064700410010026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of including whole oats into pellets on performance and plumage condition in laying hens housed in conventional and furnished cages

Abstract: In an experiment including 2400 layers, a diet with 40) whole oats incorporated into 3 mm pellets (experimental diet) was compared with a complete diet, also as 3 mm pellets, but containing no whole oats (control diet). These diets were examined in conventional 3-hens cages and two furnished cage systems with 8 or 16 birds per group including nest, perches and litter. The effects of diet, rearing condition and cage system on performance, plumage condition, comb lesions and rear body wounds were studied. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…This experimental design allowed for four rearing and housing combinations: CR/CC; CR/FC; FR/CC; and FR/FC. This study was part of another largescale study (Hetland et al, 2004), and the results reported here are from a total of 160 individuals randomly selected from these rearing and housing alternatives, that is, 80 birds (20 per rearing and housing alternative) for the ACTH and immunization challenge, and a further 80 birds (20 per rearing and housing alternative) for the H/L trial. Individual hens were not marked according to rearing pen or cage number when they were transferred to layers cage systems, and it was therefore not possible to include pen or rearing cage number as a factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental design allowed for four rearing and housing combinations: CR/CC; CR/FC; FR/CC; and FR/FC. This study was part of another largescale study (Hetland et al, 2004), and the results reported here are from a total of 160 individuals randomly selected from these rearing and housing alternatives, that is, 80 birds (20 per rearing and housing alternative) for the ACTH and immunization challenge, and a further 80 birds (20 per rearing and housing alternative) for the H/L trial. Individual hens were not marked according to rearing pen or cage number when they were transferred to layers cage systems, and it was therefore not possible to include pen or rearing cage number as a factor.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that rearing pullets with intact beaks on deep litter floor resulted in a positive long-term impact on plumage conditions regardless of housing conditions (i.e. FC or CC) during the laying period (Hetland et al, 2004). Hens for this study had been recruited from that large-scale experiment in order to explore measures relevant to stress and adaptation that have been presented as an important approach for addressing hen welfare (Blokhuis et al, 2007).…”
mentioning
confidence: 99%
“…A full crop and gizzard is likely to make the birds feel more satiated, resulting in birds appearing more calm. This may contribute to a lower feather pecking pressure (Hartini et al, 2003;Hetland et al, 2004b). The effects of insoluble NSP intake on MRT in the foregut were more pronounced with coarse vs fine ground NSP.…”
Section: Effect Of Particle Sizes Of Nspmentioning
confidence: 99%
“…Appleby and Hughess (1991) stated that no system was ideal from the aspect of production, welfare, layers' health, and mortality. Hetland et al (2004) compared 2 400 layers in conventional 3-hen cages and two furnished cage systems with 8 or 16 birds. Egg production was lower in furnished cages than in conventional cages.…”
mentioning
confidence: 99%